Immunoreactivities Against Different Tyrosine-Phosphatase 2 (IA-2)(256-760) Protein Domains Characterize Distinct Phenotypes in Subjects With LADA - Tiberti, Claudio; D’Onofrio, Luca; Panimolle, Francesca; Zampetti, Simona; Maddaloni, Ernesto; Buzzetti, Raffaella (Frontiers in Endocrinology, 2022)
Antibodies(Abs) against intracellular epitopes of the tyrosine-phosphatase 2 (IA-2) are detected in type 1 diabetes. Abs directed against the IA-2(256-760) portion, with both intra- and extracellular epitopes, are present in people with latent autoimmune diabetes in adults (LADA) and in obese subjects with normal glucose tolerance (NGT). We aim to characterize distribution and clinical features of intra- and extra-cellular IA-2(256-760) immunoreactivities in people with LADA compared to obese people with NGT. The intracellular immunoreactivity represented by immune response against two intracellular IA-2 constructs (IA-2JM(601-630) and IA-2IC(605-979)) was analyzed and related to clinical and biochemical features in 101 people with LADA and in 20 NGT obese subjects, all testing positive for IA-2(256-760)Abs. IA-2 intracellular immunoreactivity showed a frequency of 40.6% in LADA while it was not detected among NGT obese (p<0.001). Amongst LADA, the presence of immunoreactivity against the IA-2 intracellular domains was associated with lower BMI, waist circumference, higher HDL cholesterol and lower triglycerides, lower prevalence of hypertension and higher prevalence of other autoimmune disorders. Immunoreactivity against IA-2 does not involve intracellular domains in the majority of LADA and in obese people with NGT. This study shows that there is heterogeneity in the IA-2 epitopes, associated with different clinical features.